2019
DOI: 10.1136/bmjhci-2019-000014
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of data source and interoperability messaging on health information technology (HIT) users: a study series from the United States Department of Veterans Affairs

Abstract: BackgroundThe promise of Health Information Exchange (HIE) systems rests in their potential to provide clinicians and administrative staff rapid access to relevant patient data to support judgement and decision-making. However, HIE systems can have usability and technical issues, as well as fail to support user workflow.ObjectiveShare the findings from a series of studies that address HIE system deficiencies for an Electronic Health Record (EHR) viewer which accesses multiple data sources.MethodsA variety of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…, concerning computerised provider order entry (CPOE) systems used alongside EHRs in many hospital settings, found that usability problems contributed to nearly 97% of medication-related errors, with data entry and workflow support being the two most common types of usability issues [ 53 ]. Similarly, other design limitations such as the failure to support clinical workflow and unresponsive/slow systems have also been previously recognised [ 54 56 ]. In a systematic review by Mello et al ., the lack of consensus regarding terminology, classification, communication, and data transfer standards, all well-recognised problems, remain notable hurdles to interoperability today [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…, concerning computerised provider order entry (CPOE) systems used alongside EHRs in many hospital settings, found that usability problems contributed to nearly 97% of medication-related errors, with data entry and workflow support being the two most common types of usability issues [ 53 ]. Similarly, other design limitations such as the failure to support clinical workflow and unresponsive/slow systems have also been previously recognised [ 54 56 ]. In a systematic review by Mello et al ., the lack of consensus regarding terminology, classification, communication, and data transfer standards, all well-recognised problems, remain notable hurdles to interoperability today [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication by Adams et al, concerning computerised provider order entry (CPOE) systems used alongside EHRs in many hospital settings, found that usability problems contributed to nearly 97% of medication-related errors, with data entry and work ow support being the two most common types of usability issues [54]. Similarly, other design limitations such as the failure to support clinical work ow and unresponsive/slow systems have also been previously recognised [55][56][57]. In a systematic review by Mello et al, the lack of consensus regarding terminology, classi cation, communication, and data transfer standards, all well-recognised problems, remain notable hurdles to interoperability today [17].…”
Section: Comparison With Prior Workmentioning
confidence: 99%